2018
DOI: 10.1002/ptr.6199
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the neuroprotective perspectives of beta‐caryophyllene

Abstract: Beta (β)-caryophyllene (BCAR) is a major sesquiterpene of various plant essential oils reported for several important pharmacological activities, including antioxidant, anti-inflammatory, anticancer, cardioprotective, hepatoprotective, gastroprotective, nephroprotective, antimicrobial, and immune-modulatory activity. Recent studies suggest that it also possesses neuroprotective effect. This study reviews published reports pertaining to the neuropharmacological activities of BCAR. Databases such as PubMed, Scop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(83 citation statements)
references
References 110 publications
(106 reference statements)
1
79
0
3
Order By: Relevance
“…It has also been demonstrated that BCP, at the dose of 10 mg/kg, inhibits the transcription of iNOS, IL-1β, IL-6, and COX-2 in C6 microglia cells [9,24].…”
Section: β-Caryophyllene and Nervous Systemmentioning
confidence: 97%
See 4 more Smart Citations
“…It has also been demonstrated that BCP, at the dose of 10 mg/kg, inhibits the transcription of iNOS, IL-1β, IL-6, and COX-2 in C6 microglia cells [9,24].…”
Section: β-Caryophyllene and Nervous Systemmentioning
confidence: 97%
“…In the last few years, BCP has represented an important subject of study [9][10][11][12][13][14][15]. In particular, a lot of researches about the its effects in vitro and in vivo on animals have been conducted, thus experimental data about its biological properties have been verified.…”
Section: Biological Properties Of β-Caryophyllenementioning
confidence: 99%
See 3 more Smart Citations